Validation Behavioural Academic Confidence Scale on Indonesia College Student - Arjanggi, Ruseno; Hartono,; Adnjani, Made Dwi; Sholihah, Hidayatus (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to validate Academic Behavioural Confidence (ABC) scales for students in Indonesia. Academic behavioural confidence scales are useful to help teachers understand their students and organize effective learning models. The scale of academic behavioural confidence original consists of 24 items which consist of six components namely: grade, studying, verbalizing, attendance, understanding, and requesting. The participants of this study were students at A private university in Semarang, total research participants 753 students. Using exploratory factor analysis found a different component compared to the findings of the previous study, namely the understanding component, so that in this study four components formed the scale of academic behavioural confidence, namely: grade, verbalizing, studying, and understanding.